Electrical muscle stimulation elevates intramuscular BDNF and GDNF mRNA following peripheral nerve injury and repair in rats. (15th October 2016) - Willand, Michael P.; Rosa, Elyse; Michalski, Bernadeta; Zhang, Jennifer J.; Gordon, Tessa; Fahnestock, Margaret; Borschel, Gregory H.
Highlights: Daily electrical muscle stimulation enhanced early reinnervation after nerve injury. GDNF and BDNF mRNA are upregulated in muscle but not distal stump with stimulation. Muscle-derived GDNF and BDNF may contribute to enhanced reinnervation after injury. Abstract: Despite advances in surgery, patients with nerve injuries frequently have functional deficits. We previously demonstrated in a rat model that daily electrical muscle stimulation (EMS) following peripheral nerve injury and repair enhances reinnervation, detectable as early as two weeks post-injury. In this study, we explain the enhanced early reinnervation observed with electrical stimulation. In two groups of rats, the tibial nerve was transected and immediately repaired. Gastrocnemius muscles were implanted with intramuscular electrodes for sham or muscle stimulation. Muscles were stimulated daily, eliciting 600 contractions for one hour/day, repeated five days per week. Sixteen days following nerve injury, muscles were assessed for functional reinnervation by motor unit number estimation methods using electromyographic recording. In a separate cohort of rats, surgical and electrical stimulation procedures were identical but muscles and distal nerve stumps were harvested for molecular analysis. We observed that stimulated muscles had significantly higher motor unit number counts. Intramuscular levels of brain-derived and glial cell line-derived neurotrophic factor (BDNF and GDNF) mRNA were significantly upregulated in muscles that underwent daily electrical stimulation compared to those without stimulation. The corresponding levels of trophic factor mRNA within the distal stump were not different from one another, indicating that the intramuscular electrical stimulus does not modulate Schwann cell-derived trophic factor transcription. Stimulation over a three-month period maintained elevated muscle-derived GDNF but not BDNF mRNA. In conclusion, EMS elevates intramuscular trophic factor mRNA levels which may explain how EMS enhances neural regeneration following nerve injury.